2000
DOI: 10.1007/s002109900156
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis toxin suppresses carbachol-evoked cardiodepression but does not modify cardiostimulation mediated through β1- and putative β4-adrenoceptors in mouse left atria: no evidence for β2- and β3-adrenoceptor function

Abstract: Activation of beta1-, beta2-, beta 3- and putative beta4-adrenoceptors modifies cardiac function. These receptors are usually coupled to Gs protein, but beta2- and beta3-adrenoceptors could also couple to Gi/o proteins. The mouse heart is used increasingly for studies of genetically disrupted or overexpressed proteins, including beta-adrenoceptor subtypes. We therefore investigated in contracting mouse left atria (2 Hz, 37 degrees C) if inactivation of Gi/o proteins with pertussis toxin modifies or uncovers ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Also, the expression of α 1A -adrenoceptor mRNA was not regularly recorded and it is conceivable that species differences may exist (for review see Brodde and Michel, 1999). In respect to β 3 -adrenoceptors, while majority of authors (for review see Gauthier et al, 2000) have determined the β 3 -adrenoceptors functionally and also found their mRNA, the others (Kaumann and Molenaar, 1997;Oostendorp and Kaumann, 2000) have found only marginal effects of β 3 -adrenoceptor specific agonist on heart function. Moreover, Evans et al (1996), Berkowitz et al (1995) and Krief et al (1993) were not able to identify β 3 -adrenoceptor mRNA in the heart.…”
Section: Discussionmentioning
confidence: 97%
“…Also, the expression of α 1A -adrenoceptor mRNA was not regularly recorded and it is conceivable that species differences may exist (for review see Brodde and Michel, 1999). In respect to β 3 -adrenoceptors, while majority of authors (for review see Gauthier et al, 2000) have determined the β 3 -adrenoceptors functionally and also found their mRNA, the others (Kaumann and Molenaar, 1997;Oostendorp and Kaumann, 2000) have found only marginal effects of β 3 -adrenoceptor specific agonist on heart function. Moreover, Evans et al (1996), Berkowitz et al (1995) and Krief et al (1993) were not able to identify β 3 -adrenoceptor mRNA in the heart.…”
Section: Discussionmentioning
confidence: 97%
“…However, it has also recently been suggested that the contribution of h 2 or h 3 adrenoreceptor signaling to the inotropic and HR response to physiological h-agonists in murine atria may be negligible under these conditions [41]. Furthermore, the h 1 signaling pathway, which may play a dominant role in physiological hadrenergic responsiveness, is not affected by acute Giblockade (for < 24 h) with PTx [43], suggesting the cardioinhibitory effects we see develop over the course of the 3 day incubation period, during which time eNOS gene upregulation occurs.…”
Section: Enos-dependent Regulation Of Cardiac B-adrenergic Responsivementioning
confidence: 94%
“…Spontaneously beating right atria, left atria and the free wall of the right ventricle were rapidly dissected, mounted in pairs and attached to Swema 4‐45 strain gauge transducers in an apparatus containing modified Tyrode's solution at 37 °C. Left atria and right ventricular walls were paced at 2 Hz and stretched as described ( Oostendorp and Kaumann, 2000 ; Heubach et al , 2002 ). Contractile force was recorded through PowerLab amplifiers on a Chart for Windows, version 5.0 recording programme (ADInstruments, Castle Hill, NSW, Australia).…”
Section: Methodsmentioning
confidence: 99%